Totipotency of mouse zygotes extends to single blastomeres of embryos at the four-cell stage - Marino Maemura (Nature Portfolio, 2021)
Abstract In multicellular organisms, oocytes and sperm undergo fusion during fertilization and the resulting zygote gives rise to a new individual. The ability of zygotes to produce a fully formed individual from a single cell when placed in a supportive environment is known as totipotency. Given that totipotent cells are the source of all multicellular organisms, a better understanding of totipotency may have a wide-ranging impact on biology. The precise delineation of totipotent cells in mammals has remained elusive, however, although zygotes and single blastomeres of embryos at the two-cell stage have been thought to be the only totipotent cells in mice. We now show that a single blastomere of two- or four-cell mouse embryos can give rise to a fertile adult when placed in a uterus, even though blastomere isolation disturbs the transcriptome of derived embryos. Single blastomeres isolated from embryos at the eight-cell or morula stages and cultured in vitro manifested pronounced defects in the formation of epiblast and primitive endoderm by the inner cell mass and in the development of blastocysts, respectively. Our results thus indicate that totipotency of mouse zygotes extends to single blastomeres of embryos at the four-cell stage.